THE IMPLEMENTATION OF TEACHING WRITING SKILL THROUGH ‘SCRATCH’ FOR EIGHTH GRADE STUDENTS AT SMP SWASTA AL HIKMAH MEDAN - Nur Arfa Dila; Safrida Lubis (Universitas Negeri Medan, 2022)
The aims of the research are to describe the students’ problems in writing and to describe the effective of the implementation of teaching writing skills through the Scratch program. This study was designed descriptive qualitative. The data in this study were obtained through questionnaire and interview. The subjects of the study were an English teacher and twenty eighth-grade students of SMP Swasta Al-Hikmah Medan. The students' problems are lack of vocabulary in writing, lack of confidence in creating ideas, lack of interest in learning English, and students' perceptions of ineffective strategies. According to the teacher scratch program is effective to use in teaching writing skills. Based on the results, the use of the Scratch program in teaching writing skills deserves to be used as an interesting and creative learning media.